Analisis Yuridis Perlindungan Hukum Rahasia Dagang Produksi Kopi Bubuk Dalam Putusan Mahkamah Agung Nomor 332k/Pid.Sus/2013 - Azizah Arfah; Raka Haikal; Hendra Parulian; Albert S. Limbong; Maulida Fitriani; Irwan Triadi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Appreciation of IPR in Indonesia is still relatively low and many people consider IPR to be unimportant and even many lay people do not understand IPR. One of them is the protection of trade secrets which plays an important role for both personal and public interests. The research method is normative legal with prescriptive data analysis. Trade secrets cover aspects of pre-production to post-production, including marketing and sales. The use of trade secrets without permission and approval from other parties is a violation of Law Number 30 of 2000 concerning Trade Secrets. The use of information includes production methods, frying, grinding, to marketing and sales of CV ground coffee. Tiga Putra Berlian resembles CV. Bintang Harapan by recruiting employees, offering coffee products that have been produced to CV customers. Bintang Harapan, causing losses and violating Article 17 of Law Number 30 of 2000.